Property-based Object Management and Security - Reiners, Torsten; Wriedt, S.; Rea, A. (IGI Global, 2011)
The hype of Second Life is over. But the experience of this truly exciting period lives on in many disciplines and research areas, which are developing emerging technologies in virtual, as well as augmented worlds. And as is the rule with new forming developments, the path is not yet determined and weaves through different stages and platforms, calling for additional prototypes to understand the true impact of virtual worlds, Web 3D, or Augmented Reality. Using broad strokes and looking for a common denominator, most people conclude that it is Web 2.0 with all its (social) functionality and 3D objects as the embodiment of virtual existence. Many publications discuss Web 2.0 features and applications, but most do not focus on the 3D objects in the context of virtual worlds and their implications. In this chapter, the authors examine and observe what (virtual) objects are, as well as which properties should be used for inter-world interoperability. The past technological implementations demonstrate that protecting digital media – i.e. music and video – is an endless endeavor and that no security feature is simultaneously unbreakable and usable. This does not need to be the case for 3D virtual objects because we can learn from the past and achieve a new level of protection in a rising media. In this chapter the authors propose such a solution by putting forth a general 3D object understanding that includes a look at virtual worlds such as Second Life with a feasible concept of object security. They suggest that with a new framework objects can be secured and promote additional growth within, and among, virtual worlds. They propose our Global Object Management System (GOMS) architecture as a potential solution to this challenge.